Recurrence of esophageal varices after endoscopic band ligation: single centre experience - MAŠALAITĖ, Laura; VALANTINAS, Jonas; STANAITIS, Juozas (Acta medica Lituanica, 2012)
Background and objective. Endoscopic band ligation is the main endoscopic treatment for esophageal varices, but the main problem after endoscopic treatment is variceal recurrence. The aim of this study was to evaluate and determine the esophageal varices recurrence rate and the time interval after endoscopic band ligation and to investigate possible risk factors affecting recurrence.Material and methods. The retrospective analysis of endoscopic band ligation procedures, performed in Vilnius University Hospital Santariskiu Clinics during the period 2006–2010, was made. 133 endoscopic band ligation procedures were included in the study.Results. After endoscopic band ligation, esophageal varices recurred in 45% of cases. The early recurrence of esophageal varices occurred in 46.7% of cases. Extrahepatic portal hypertension and a greater size of varices lead to the statistically significant early recurrence of esophageal varices after endoscopic band ligation.Conclusions. Endoscopic band ligation is associated with a high recurrence rate of esophageal varices and half of these cases were indentified as early variceal recurrence.